Permainan Simulasi Kencan sebagai Medium Romantic Loneliness - Sarah Noverianti; Ardian Indro Yuwono (Universitas Gadjah Mada, 2021)
Dating simulation game is a subgenre of simulation game, where the player—who plays as the main character surrounded by many male/female characters—interact with the game character to develop romantic relationship with one of them, through the multiple choice feature in the game. This feature will bring the gamer to a fantasy where they can meet someone who gives affection and love to them, and could date with them. Through ethnography method, this article investigate on the process and experience of playing the game to overcome their romantic loneliness by the gamers of “Mystic Messenger” (for female gamer) and “If My Heart Had Wings” (for male gamer). The results shows that the playing process is centered on the interaction’s process between gamers and the game characters, through conversation dialogue and the multiple choice feature, as well as various features in the game. This process brings the gamer to be close to the character their chose, thus providing an ideal romantic relationship experience for gamers, as if they were interacting and establishing a relationship with real people.